Catholic cosmopolitanism and human rights / Leonard Francis Taylor. - Taylor, Leonard Francis, 1970- (Cambridge University Press, 2020)
It is because Catholicism played such a formative role in the construction of Western legal culture that it is the focal point of this enquiry. The account of international law from its origin in the treaties of Westphalia, and located in the writing of the Grotian tradition, had lost contact with another cosmopolitan history of international law that reappeared with the growth of the early twentieth century human rights movement. The beginnings of the human rights movement, grounded in democratic sovereign power, returned to that moral vocabulary to promote the further growth of international order in the twentieth century. In recognising this technique of periodically returning to Western cosmopolitan legal culture, this book endeavours to provide a more complete account of the human rights project that factors in the contribution that cosmopolitan Catholicism made to a general theory of sovereignty, international law and human rights.